Editorial - Ghimire, Nani Babu (Siddhajyoti Interdisciplinary Journal, 2026)
Since 2020, the Research Management Cell (RMC) of Siddhajyoti Education Campus (SJEC) has been publishing the Siddhajyoti Interdisciplinary Journal (SIJ) with the aim of fostering academic engagement. The journal motivates scholars to investigate, articulate, and disseminate their research and scholarly perspectives. It functions as a forum for knowledge exchange among educators, researchers, students, policymakers, and practitioners from a wide range of interdisciplinary areas, including Education, Curriculum, Psychology, EPM, English, Nepali, Mathematics, Science, Social Sciences, Population Studies, Economics, Health, Physical Education, Business, Management, and Marketing. Through the systematic publication of research works, SIJ plays a vital role in strengthening scholarly dialogue across these disciplines. The seventh volume of the Siddhajyoti Interdisciplinary Journal (SIJ) comprises 21 carefully selected research articles, all of which have undergone rigorous peer review and editorial scrutiny. This volume showcases contributions from emerging Nepali scholars representing diverse fields such as English Education, English Literature, Nepali, Education, Population Studies, Health Education, and Social Studies. The studies presented here offer rich perspectives and collectively form a valuable knowledge base for future multidisciplinary practitioners in Nepal, reflecting the journal’s commitment to academic diversity and research excellence